2017
DOI: 10.1021/acs.analchem.7b03830
|View full text |Cite
|
Sign up to set email alerts
|

Structural and Functional Characterization of a Hole–Hole Homodimer Variant in a “Knob-Into-Hole” Bispecific Antibody

Abstract: Bispecific antibodies have great potential to be the next-generation biotherapeutics due to their ability to simultaneously recognize two different targets. Compared to conventional monoclonal antibodies, knob-into-hole bispecific antibodies face unique challenges in production and characterization due to the increase in variant possibilities, such as homodimerization in covalent and noncovalent forms. In this study, a storage- and pH-sensitive hydrophobic interaction chromatography (HIC) profile change was ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
38
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 35 publications
(41 citation statements)
references
References 34 publications
3
38
0
Order By: Relevance
“…KiH (H) was chosen as a recipient for the D84.4Q substitution over KiH "knob" (denoted K; T366W) because we found its characteristics to be the closest match to BEAT (B); both KiH (H) and BEAT (B) are the chains receiving the smaller residues, creating cavities to accommodate the larger residues introduced into KiH (K) and BEAT (A). Furthermore, some characterization data for KiH (H) homodimers had been published (13). Upon purification, we found that this antibody was not abrogated for PA binding (Fig.…”
Section: D844q Substitution Abrogates Pa and Pg Binding In The Fc Ofmentioning
confidence: 65%
See 3 more Smart Citations
“…KiH (H) was chosen as a recipient for the D84.4Q substitution over KiH "knob" (denoted K; T366W) because we found its characteristics to be the closest match to BEAT (B); both KiH (H) and BEAT (B) are the chains receiving the smaller residues, creating cavities to accommodate the larger residues introduced into KiH (K) and BEAT (A). Furthermore, some characterization data for KiH (H) homodimers had been published (13). Upon purification, we found that this antibody was not abrogated for PA binding (Fig.…”
Section: D844q Substitution Abrogates Pa and Pg Binding In The Fc Ofmentioning
confidence: 65%
“…The increase in Rh was less significant than for the BEAT (B) D84.4Q homodimers. Zhang et al ( 13 ) attributed the increase in Rh of the KiH (H) homodimer to a reduced compactness of the domains caused by their poor pairing capabilities. This also may explain the relatively mild reduction in FcRn and FcγR1a binding compared with the corresponding KiH heterodimer ( Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Native MS utilizes 100% aqueous solutions of low-to-moderate concentrations of volatile salt (e.g., 50 mM ammonium acetate) buffered at neutral pH. 3,4 This type of analysis proceeds commonly after removal of non-volatile salts by buffer exchange followed by nanospray infusion MS. 57 Native MS-based intact mass analysis is required for certain classes of biotherapeutics that require preservation of non-covalent associations of protein-protein or protein-ligand complexes. 8 Native MS also affords a fundamental benefit to intact mass analysis of all types of heterogeneous samples where proteins acquire fewer charges and yield spectra at high m/z relative to denatured conditions.…”
Section: Introductionmentioning
confidence: 99%